Umbilical Cord Blood Leptin and IL-6 in the Presence of Maternal Diabetes or Chorioamnionitis - Vasilakos, Lauren K.; Steinbrekera, Baiba; Santillan, Donna A.; Santillan, Mark K.; Brandt, Debra S.; Dagle, Daniel; Roghair, Robert D. (Frontiers in Endocrinology, 2022)
Diabetes during pregnancy is associated with elevated maternal insulin, leptin and IL-6. Within the placenta, IL-6 can further stimulate leptin production. Despite structural similarities and shared roles in inflammation, leptin and IL-6 have contrasting effects on neurodevelopment, and the relative importance of maternal diabetes or chorioamnionitis on fetal hormone exposure has not been defined. We hypothesized that there would be a positive correlation between IL-6 and leptin with progressively increased levels in pregnancies complicated by maternal diabetes and chorioamnionitis. To test this hypothesis, cord blood samples were obtained from 104 term infants, including 47 exposed to maternal diabetes. Leptin, insulin, and IL-6 were quantified by multiplex assay. Factors independently associated with hormone levels were identified by univariate and multivariate linear regression. Unlike IL-6, leptin and insulin were significantly increased by maternal diabetes. Maternal BMI and birth weight were independent predictors of leptin and insulin with birth weight the strongest predictor of leptin. Clinically diagnosed chorioamnionitis and neonatal sepsis were associated with increased IL-6 but not leptin. Among appropriate for gestational age infants without sepsis, IL-6 and leptin were strongly correlated (R=0.6, P<0.001). In summary, maternal diabetes and birth weight are associated with leptin while chorioamnionitis is associated with IL-6. The constraint of the positive association between leptin and IL-6 to infants without sepsis suggests that the term infant and placenta may have a limited capacity to increase cord blood levels of the neuroprotective hormone leptin in the presence of increased cord blood levels of the potential neurotoxin IL-6.